Left Atrial Stiffness: A Predictor of Atrial Fibrillation Recurrence after Radiofrequency Catheter Ablation - A Systematic Review and Meta-Analysis - Correia,Eduardo Thadeu de Oliveira (2019)
Abstract Background: Radiofrequency catheter ablation (RFCA) is a standard procedure for patients with atrial fibrillation (AF) not responsive to previous treatments, that has been increasingly considered as a first-line therapy. In this context, perioperative screening for risk factors has become important. A previous study showed that a high left atrial (LA) pressure is associated with AF recurrence after ablation, which may be secondary to a stiff left atrium. Objective: To investigate, through a systematic review and meta-analysis, if LA stiffness could be a predictor of AF recurrence after RFCA, and to discuss its clinical use. Methods: The meta-analysis followed the MOOSE recommendations. The search was performed in MEDLINE and Cochrane Central Register of Controlled Trials databases, until March 2018. Two authors performed screening, data extraction and quality assessment of the studies. Results: All studies were graded with good quality. A funnel plot was constructed, which did not show any publication bias. Four prospective observational studies were included in the systematic review and 3 of them in the meta-analysis. Statistical significance was defined at p value < 0.05. LA stiffness was a strong independent predictor of AF recurrence after RFCA (HR = 3.55, 95% CI 1.75-4.73, p = 0.0002). Conclusion: A non-invasive assessment of LA stiffness prior to ablation can be used as a potential screening factor to select or to closely follow patients with higher risks of AF recurrence and development of the stiff LA syndrome.